A revisão do moderno e a revisitação do vernáculo : uma leitura sobre as geometrias da Pousada de Oliveira do Hospital, de Manuel Tainha - Rodeia, Teresa Maria Ribeiro Belo, 1964- (2021)
The Pousada de Oliveira do Hospital, a luxury inn designed between 1954 and 1960 and built between 1968 and 1971, remains a reference in the work of the architect Manuel Tainha (1922-2012) and Portuguese architecture of the latter half of the 20th century. It emphasises the particular bond with the location; the revision of the Modern Movement experience based on the revisitation of the vernacular culture; the permanent rediscovery of the landscape made available by its spaces, which was at the same time the first challenge and the ultimate goal of the design project. In the pousada one perceives the singular relationship Tainha had with drawing, through observing the game of deliberate complexity that only experience of the work enables one to confirm as correct. Acknowledgment of this game is the grounds for assessment of the importance of geometry in the definition of the pousada’s design. Geometry emerges as a relational guarantee for the various elements that make up the building, manifesting itself as a structuring scheme for the space and for the configurations that make up the space, as a planimetric modular system, or as an archetypal configuration, at all times intimately linked with the expectation of its realisation as a built form; for this reason, the definition of the concrete geometries is tied to the construction systems used – continuous granite stone work and schist columns, on the one hand; and reinforced concrete pillars, beams and slabs, on the other. The affirmation of the rule in the form of a reinforced concrete structure – an obvious nod to the Modern, even if it was undergoing revision – is offset by the subversion of the rule through the massive use of local granite, which is a testament to the vernacular that was then beginning to be revisited. This essay sets out to assess the importance of geometry in the design project for the Pousada de Oliveira do Hospital, constituting an examination that goes beyond the mere instrumental scope.